2006
DOI: 10.1093/jat/30.8.599
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate-Positive Death-Investigation and Impaired-Driving Cases in Washington State

Abstract: Topiramate (Topamax), an effective seizure disorder treatment, received additional FDA approval for prevention of migraine headaches in August 2004 and has gained attention for its off-label uses, including psychiatric and eating disorders, neuropathic pain, and alcohol and drug dependency. Side effects of sedation, dizziness, ataxia, speech difficulty, nystagmus, paresthesia, and metabolic acidosis are described. The manufacturer reports that tolerance to the antiseizure properties does not develop. With its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…One gross effect of TPM on daily life has been evaluated by examining motor vehicle performance and at least two studies have found TPM-related decreases in driving ability 72,78. In one, a subsample of patients with partial seizures taking part in a randomized, double-blind, controlled study comparing the cognitive effects of TPM and LTG, was administered a computerized task measuring scanning, divided attention, and effective field of view (via the Performance On-Line, or POL) 72.…”
Section: Tpm Effects On Cognitionmentioning
confidence: 99%
“…One gross effect of TPM on daily life has been evaluated by examining motor vehicle performance and at least two studies have found TPM-related decreases in driving ability 72,78. In one, a subsample of patients with partial seizures taking part in a randomized, double-blind, controlled study comparing the cognitive effects of TPM and LTG, was administered a computerized task measuring scanning, divided attention, and effective field of view (via the Performance On-Line, or POL) 72.…”
Section: Tpm Effects On Cognitionmentioning
confidence: 99%
“…In forensic toxicology investigations of topiramate-positive drivers reported by Gordon and Logan (2006), psychomotor impairment was evident with blood concentrations within normal therapeutic range. As an example, a 31-year-old female was prescribed topiramate for an eating disorder.…”
Section: Effects On Driving Of Specific Drugs/drug Classesmentioning
confidence: 96%
“…Topiramate (an anti-epileptic also used in migraine revention and other therapies) Topiramate (Topamax) is a seizure disorder treatment that received additional FDA approval for prevention of migraine headaches in August 2004, and is being prescribed for offlabel uses such as psychiatric disorders (e.g., schizophrenia and bi-polar disorder); eating disorders (e.g., bulimia, binge eating, obesity, and anorexia nervosa); as an adjunct therapy to treat weight gain associated with olanzapine, SSRIs, and other anti-psychotic medications; neuropathic pain; and alcohol and drug dependency (Gordon & Logan, 2006). Its potentially driver impairing side effects include sedation; dizziness; confusion; difficulty concentrating; shaky and unsteady body movements; rapid and repetitious involuntary eye movements; decreased visual acuity; hypoglycemia leading to loss of consciousness; and tingling or numbness in the arms and legs.…”
Section: Effects On Driving Of Specific Drugs/drug Classesmentioning
confidence: 99%
“…The Washington State Toxicology Laboratory reported data regarding topiramate-positive death investigation and impaired-driving cases 43. Topiramate-positive findings have increased in this area because of the additional prescriptions for offlabel use of topiramate.…”
Section: Introductionmentioning
confidence: 99%
“…Topiramate-positive findings have increased in this area because of the additional prescriptions for offlabel use of topiramate. From 1998 to 2004, the laboratory reported 63 death investigations, 68 suspected impaired drivers, and one sexual assault case 43. The mean reported serum topiramate concentration is 8.4 mg/L.…”
Section: Introductionmentioning
confidence: 99%